Non-Destructive Spectroscopic Assessment of High and Low Weight Bearing Articular Cartilage Correlates with Mechanical Properties. (October 2019) - Karchner, James P.; Yousefi, Farzad; Bitman, Stephanie R.; Darvish, Kurosh; Pleshko, Nancy
Objective: Autologous articular cartilage (AC) harvested for repair procedures of high weight bearing (HWB) regions of the femoral condyles is typically obtained from low weight bearing (LWB) regions, in part due to the lack of non-destructive techniques for cartilage composition assessment. Here, we demonstrate that infrared fiber optic spectroscopy can be used to non-destructively evaluate variations in compositional and mechanical properties of AC across LWB and HWB regions. Design: AC plugs ( N = 72) were harvested from the patellofemoral groove of juvenile bovine stifle joints, a LWB region, and femoral condyles, a HWB region. Near-infrared (NIR) and mid-infrared (MIR) fiber optic spectra were collected from plugs, and indentation tests were performed to determine the short-term and equilibrium moduli, followed by gravimetric water and biochemical analysis. Results: LWB tissues had a significantly greater amount of water determined by NIR and gravimetric assay. The moduli generally increased in tissues from the patellofemoral groove to the condyles, with HWB condyle cartilage having significantly higher moduli. A greater amount of proteoglycan content was also found in HWB tissues, but no differences in collagen content. In addition, NIR-determined water correlated with short-term modulus and proteoglycan content ( R = −0.40 and −0.31, respectively), and a multivariate model with NIR data was able to predict short-term modulus within 15% error. Conclusions: The properties of tissues from LWB regions differ from HWB tissues and can be determined non-destructively by infrared fiber optic spectroscopy. Clinicians may be able to use this modality to assess AC prior to harvesting osteochondral grafts for focal defect repair.